In the Eye of the Storm: Bi-Directional Electrophysiological Investigation of the Intact Retina - Vėbraitė, Ieva; Hanein, Yael (Frontiers in Neuroscience, 2022)
Electrophysiological investigations reveal a great deal about the organization and function of the retina. In particular, investigations of explanted retinas with multi electrode arrays are widely used for basic and applied research purposes, offering high-resolution and detailed information about connectivity and structure. Low-resolution, non-invasive approaches are also widely used. Owing to its delicate nature, high-resolution electrophysiological investigations of the intact retina until now are sparse. In this Mini Review, we discuss progress, challenges and opportunities for electrode arrays suitable for high-resolution, multisite electrophysiological interfacing with the intact retina. In particular, existing gaps in achieving bi-directional electrophysiological investigation of the intact retina are discussed.